Secosterol-B affects endoplasmic reticulum structure in endothelial cells. Issue 190 (June 2019) - Luchetti, Francesca; Crinelli, Rita; Nasoni, Maria Gemma; Cesarini, Erica; Canonico, Barbara; Guidi, Loretta; Zerbinati, Chiara; Magnani, Mauro; Papa, Stefano; Iuliano, Luigi
Graphical abstract: Highlights: Secosterol-B induces ER stress in HUVEC. Secosterol-B triggers pro-survival signaling through autophagy and UPS. eIF2α phosphorylation and NF-kB activation involved in the secosterol-B-induced apoptosis. Abstract: Oxysterols, oxidized derivatives of cholesterol found in LDL and atherosclerotic plaques, trigger several biological responses involved in the initiation and progression of atherosclerosis. Endothelial dysfunction, which occurs when vascular homeostasis is altered, plays a key role in the pathogenesis of several metabolic diseases. The contribution of endoplasmic reticulum (ER) stress to endothelial disfunction is a relatively recent area of investigation. There is a well-established link between LDL oxidation and ER stress but the role played by specific products of lipid oxidation into this interaction is still to be defined. The present study shows that secosterol-B (SEC-B), 3β-hydroxy-5β-hydroxy-B-norcholestane-6βcarboxaldehyde, a cholesterol autoxidation product recently identified in the atherosclerotic plaque, is able to induce ER stress in HUVEC cells, as revealed by significant expansion and change of structure. At low doses, i.e. 1 and 5 μM, cells try to cope with this stress by activating autophagy and the ubiquitin proteasome system in the attempt to restore ER function. However, at higher doses, i.e. 20 μM, cell apoptosis occurs in a pathway that involves early phosphorylation of eIF2α and NF-kB activation, suggesting that the adaptive program fails and the cell activates the apoptotic program. These findings provide additional insight about the role of oxysterols in endothelial dysfunction and its potential involvement in atherosclerotic pathophysiology.